NANOTECHNOLOGY BASED TARGETED DRUG DELIVERY SYSTEMS IN BREAST CANCER THERAPY (Proceedings of International Conference on BioScience and Biotechnology, 2017)
Cancer is a highly heterogeneous and complex disease condition to understand because of its cellular and physiological systems. The most common cancer treatments are chemotherapy, radiotherapy and surgical excision. Out of them chemotherapy remains as the most widely used anti-cancer therapy. But unfortunately chemotherapy has plenty of drawbacks when considering its action on cancerous cells. Many chemotherapeutic drugs are highly toxic, not specific, poorly selective and less soluble because of these incidents cancer patients have severe side effects such as alopecia, renal failures, cardiac failures and etc. In order to overcome these problems in nanotechnology based targeted drug delivery system was introduced. Nanotechnology is a rapidly growing files which promote novel methods in cancer diagnosis, treatments and prognosis. In targeted drug delivery system use differently synthesized nanoparticles to reduce the drawbacks of chemotherapy. Nanoparticles such as liposomes, carbon nanotubes, virus mediated nanoparticles and nanodiamonds are some of the nanoparticles which are being discussed in this article. By using nanoparticles many of the drawbacks in conventional chemotherapy can be altered for an example by using surface functionalized nanoparticles chemotherapeutic drugs can be loaded into the particle and easily can be delivered to the exact tumor site without harming the non-cancerous cells while increasing the halflife of the drug. Likewise there are many advantages in nanotaenology based targeted drug delivery system over the conventional chemotherapy which will give a new ray of hope towards cancer patients to have a quality life.
Keywords: Nanotecnology; Targeted Drug Delivery; Nanoparticles; Active Targeting; Passive Targeting; Cancer